AVERAGE HEAT TRANSFER OF TUBES IN DOWNWARD FOAM FLOW - Gylys, J.; Jakubcionis, M.; Sinkunas, S.; Zdankus, T. (Revista de Engenharia Térmica, 2003)
The model of heat exchanger was investigated experimentally. This model consists of three vertical lines of horizontal tubes with five tubes in each. Tubes were arranged in a staggered order. Heat transfer of staggered bundle of tubes to downward static stable foam flow was investigated experimentally. Heat transfer dependence on specific gas and liquid velocity was determined. Dependence of volumetric void fraction of foam on heat transfer was investigated also. Heat transfer rate dependence on tube position in the line of tube bundle was investigated experimentally. It was established that heat transfer rate highly depends on tube position in the line. Influence of tube position on heat transfer from tube bundle in upward foam flow was compared. Heat transfer dependence on tube position in the bundle was investigated experimentally also. Influence of wall of foam generator on heat transfer to sideline of tubes was established. Experimental results of heat transfer of bundle of tubes to downward static stable foam flow were generalized using dependence between Nusselt and Reynolds numbers.